ROUTE OPTIMIZATION FOR LPG DISTRIBUTION - ABDUL MUBAROK - 29116408, MUHAMMAD
operating in Karawang and Purwakarta areas with different sub agents. In the process of delivery or distribution of that LPG there are costs by the company, such as transportation costs, installation of plastic wrap, and other costs. There are some opportunities to make this distribution process more efficient. After doing an analysis of the existing data, it can be said that there is a problem on the agent of PT Amanah Abadi Raya (AAR). The problem is the large amount of operational costs that in a few months exceeds that of other agents. Whereas based on the existing allocation, the number of sub-agents is not more than other agents. In some analyzes through interviews with company employees, the company spend daily cost in accordance with the distance traveled by truck drivers. There is no calculation for transportation cost. The provision of transportation cost by long distance or near and with the cost of gasoline follows fluctuations in diesel prices. There is no exact calculation of the operational costs. And one of the factors that affect the magnitude of the number of these AAR agents is the location of the sub agents that are not adjacent to each other or are in a travel circle like other agents do. Company determining route by looking at the path closest to the SPBE, but only the intuition of the estimated distance in accordance with the number of allocations every day and month. This study has objectives to provide a proposal in terms of route optimization and cost efficiency in the company. The strategy or method given is the method in determining the LPG gas delivery route located in Karawang area for the cost reduction and the accuracy of the delivery route. It provided by VRPTW, nearest neighbor, and Branch and Bound method in terms of determining the optimal route. As the result, the proposed route optimal yields good distance saving on depot 1 and depot 2. For depot 1 to produce saving distance of 151.9 km. While for depot 2 to produce saving distance of 21.45 km. For depot 1, as the result of saving distance that happened that is equal to 151.9 km, then got saving cost equal to Rp 6,984,687. While depot 2, as a result of saving distance that happened that is equal to 21.45 km, then got saving cost equal to Rp 3,537,590. And when summed from both depots, the proposed long distance can reduce the distribution cost of Rp 10,522,277 per month. It can save around 45.49% from previous cost.